Antiquity and Enlightenment Culture New Approaches and Perspectives - Loughlin, Felicity (Metaforms Ser., 2020)
Half Title -- Series Information -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Figures -- Abbreviations -- Notes on Contributors -- Part 1 Danger and Delight: Reading Ancient Literature -- Chapter 1 Pseudohistory and Metafiction in the Eighteenth Century -- 1 Pseudohistory -- 2 Metafiction -- Acknowledgements -- Bibliography -- Chapter 2 The Philosophy of Ancient Poetry: Greek Poetic Pessimism in the Voyage du jeune Anacharsis en Grèce -- 1 The Greek Ideal and Greek Pessimism between the Eighteenth and Nineteenth Centuries -- 2 Anacharsis and Philocles: Greek Pessimistic Thought and the Ode to Happiness -- 3 A Time of Transition -- Bibliography -- Part 2 Antiquity on Display: Travellers, Grand Tourists, Collectors -- Chapter 3 The "Nymphs" of the Fountain of Arethusa and the Representation of Classical Sicily in Travel Works, c.1770-1860 -- 1 The Fountain of Arethusa -- 2 Changes in Travel Narratives -- 3 Conclusion -- Bibliography -- Chapter 4 Antiquity and the Grand Tour Portrait: Rethinking the Significance of Pompeo Batoni's Use of Classical Sculpture, 1753-1762 -- 1 Early Examples of Classical Insertions -- 2 Rethinking the Significance of Batoni's Use of Antiquity -- 3 Charles John Crowle (1738-1811) -- 4 Conclusion -- Bibliography -- Chapter 5 Hidden Dimensions and Elusive Forms in Johan Zoffany's Charles Townley and Friends in his Library at Park Street, Westminster, 1781-1783, 1798 -- 1 The Painting during Townley's Lifetime -- 2 Hidden Dimensions and Elusive Forms -- 3 The Painting after Townley's Death -- 4 Conclusion -- Bibliography -- Part 3 Antiquity and National Identity: Scotland and Greece -- Chapter 6 The Scottish Heresy: George Mackenzie's Pelagian Biographies -- 1 Recovering Mackenzie -- 2 The Lives and Characters -- 3 (Semi-)Pelagianism in Early Modern Thought -- 4 Mackenzie the (Semi-)Pelagian.